KONTRIBUSI ORANG TUA TERHADAP KEMAMPUAN BACA TULIS AL-QUR’AN ANAK - Rizqina Elok Hidayati; Dian Caesarianingtyas; Annisa Rahmasari; Muhammad Sholikin (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The role of parents in accompanying children is needed, especially when they are at home. This study aims to determine how much a parent can play in the development of the skills of children who read and write al-q ur 's. These donations are in the form of helping children read and write the Koran at home on their own. The target of this research is two families in need 02/03 of the sukoharjo baki facility. The study employed qualitative field research methods. Selection of research subjects uses data-collection methods using interviews, observations, and documentaries. Based on research, keywords that: parents play an important role in raising children, children learn more quickly when parents often instill motivation, a short but effective time better than long but less effective, reading and writing the Quran will have a significant impact on the child's personality.Keywords: Children; Contribution; Parent; Read and Write Quran